Financial Literacy of Economics and non-Economics Students - Rafinda, Ascaryan; Gal, Timea (International Review of Management and Marketing, 2020)
This research aims to identify the level of financial literacy of college students in economic faculties and non-economic faculties in Indonesia. This research was conducted to determine the understanding of students’ financial literacy score in the economic and non-economic faculties. The survey was conducted to test the level of student financial literacy at various University in Indonesia. This survey used objective measures of financial literacy, and the student gets the question and gets the score based on the correct answer from participants. In total, there were 206 participants from students in Indonesia who participate in the survey. An independent sample T-Test was conducted to determine differences in the level of understanding of students in the two groups. This research found that financial literacy score is differences between economic and non-economic students. Even the economics student has higher score compare to the non-economics student, but the score still below 70% for basic personal finance questions. This research implies that student on both study field needs to get personal finance courses on campus. Keywords: Personal finance, financial literacy, College student. JEL Classification: G53 DOI: https://doi.org/10.32479/irmm.8974